Thiophene Determination in Liquid Hydrocarbons by In-line Acoustic Measurements - Nikolay V. Mukhin; Mykhailo M. Kutia (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Petroleum is a complex mixture of hydrocarbons. Sulphur is the most common heteroatom in pe-troleum and petroleum products. Its content in oil can reach 14 %. The determination of sulphur in oil and its removal is of great importance, since sulphur compounds adversely affect the quality of petroleum products and pollute the environment. Desulphurization of hydrocarbons is important in the processing of petroleum products, which needs in usage of accurate and simple methods for the sulphur-containing components determination. Most of developed methods are difficult to apply for flow online analysis, which can create difficulties in using them to monitor the content of sulphur-containing heteroatomic components in real time. Acoustic sensors are one of the possible solutions. In term of sensing of flammable liquids, the use of the acoustic methods is attractive since the analyte is not a part of an electrical measuring circuit and it is only acoustically coupled that prevents an occurrence of a spark.Objective. The purpose of the work is to study the possibilities of online flow analysis of sulphur-containing heteroatomic components using acoustic measurements. The challenge is the development of a resonator system integrated with the pipe.Materials and methods. Thiophene and oil fraction with the boundary boiling point of 100–140 oC were used to prepare the mixtures. Thiophene is a representative of sulphur-containing components, which may be included in the composition of petroleum and its derivatives. Experimental measuring equipment includes impedance analyzer, a developed sensor structure integrated with a liquid-filled pipe, a pump and a tank with a measured liquid. A theoretical analysis of sensor structure was carried out on the basis of numerical simulation using COMSOL Multiphysics software.Results. The sensor structure was designed as a combination of 2D and 1D pipe periodic arrangements to achieve high Q-factor of acoustic resonance in the flow system. The eigenmodes of the sensor structure with a liquid analyte were carried out. The characteristic of sensor structure is determined. The sensor shows good sensitivity to the thiophene content with high resolution in-line analysis. This result is achieved by limiting the energy losses of acoustic resonance in radiation along the pipe by creating a periodic structure.Conclusion. The study of acoustic properties of solutions prepared on the basis of thiophene and oil fraction with boundary boiling point 100–140 °C was performed. It shows that methods based on acoustic spectroscopy make it possible to accurately determine the concentration of heteroatomic components in gasoline mixtures, since the presence of heteroatomic components leads to a change in mechanical properties of liquid hydrocarbons mixtures. Possible applications for developed acoustic sensor are flow analysis for monitoring the quality of oil products.